A literature review of lead exposure as a risk factor for neurocognitive disorders in children and obstetric risks in pregnant women - Yudhea Dwike Fransiska (Privietlab, 2026)
Lead exposure remains a persistent environmental health concern with significant implications for maternal and child health. Children and pregnant women are particularly vulnerable due to physiological susceptibility and developmental sensitivity. This study aimed to analyze existing scientific evidence regarding lead exposure as a risk factor for neurocognitive disorders in children and obstetric risks in pregnant women through a descriptive literature review approach. A comprehensive search was conducted across international and national academic databases, including peer reviewed studies published between 2005 and 2024. Articles examining biological indicators of lead exposure, particularly blood lead levels, and reporting neurocognitive outcomes in children or obstetric outcomes in pregnant women were included. The selected studies were analyzed using narrative synthesis to identify consistent patterns, dose response relationships, and biologically plausible mechanisms. The findings indicate a consistent association between elevated blood lead levels and impaired cognitive development in children, including reduced intelligence scores, executive dysfunction, and attention related problems. Evidence also demonstrates significant relationships between maternal lead exposure and increased risks of gestational hypertension, preeclampsia, preterm birth, and low birth weight. The absence of a safe exposure threshold and the presence of intergenerational effects highlight the public health significance of lead toxicity. In conclusion, lead exposure represents a critical environmental determinant of adverse neurodevelopmental and obstetric outcomes. Preventive strategies integrating environmental regulation, maternal health surveillance, and early childhood protection are essential to mitigate long term health consequences